Limitations of Transversus Abdominis Release (TAR)—Additional Bridging of the Posterior Layer And/Or Anterior Fascia Is the Preferred Solution in Our Clinical Routine If Primary Closure is Not Possible - Hartwig Riediger; Ferdinand Köckerling (Journal of Abdominal Wall Surgery)
Background: By separating the abdominal wall, transversus abdominis release (TAR) permits reconstruction of the abdominal wall and the placement of large mesh for many types of hernias. However, in borderline cases, the mobility of the layers is inadequate, and additional bridging techniques may be required for tension-free closure. We now present our own data in this regard.Patients and Methods: In 2023, we performed transversus abdominis release on 50 patients as part of hernia repair. The procedures were carried out using open (n = 25), robotic (n = 24), and laparoscopic (n = 1) techniques. The hernia sac was always integrated into the anterior suture and, in the case of medial hernias, was used for linea alba reconstruction.Results: For medial hernias, open TAR was performed in 22 cases. Additional posterior bridging was performed in 7 of these cases. The ratio of mesh size in the TAR plane to the defect area (median in cm) was 1200cm2/177 cm2 = 6.8 in patients without bridging, and 1750cm2/452 cm2 = 3.8 in those with bridging. The duration of surgery (median in min) was 139 and 222 min and the hospital stay was 6 and 10 days, respectively. Robotic TAR was performed predominantly for lateral and parastomal hernias. These procedures took a median of 143 and 242 min, and the hospital stay was 2 and 3 days, respectively. For robotic repair, posterior bridging was performed in 3 cases.Discussion: Using the TAR technique, even complex hernias can be safely repaired. Additional posterior bridging provides a reliable separation of the posterior plane from the intestines. Therefore, the hernia sac is always available for anterior reconstruction of the linea alba. The technique can be implemented as an open or minimally invasive procedure.